AN ERROR ANALYSIS OF SIMPLE PAST TENSE IN WRITING RECOUNT TEXT BY THE TENTH GRADE STUDENTS OF SMA NEGERI 2 DOLOKSANGGUL - Putri Simbolon; Masitowarni Siregar; Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2019)
The purpose of this study is to describe the errors in simple past tense of recount text. In addition, this study is also aimed to describe the causes of those errors. This study apllied the descriptive qualitative approach of which the data were obtained from the recount texts that were written by the tenth grade students of SMA Negeri 2 Doloksanggul. The data were collected by using students’ recount texts and interview. The data then were analyzed by identifying the errors first, then describing the errors, and the last explaining the errors. The errors that occurred in students’ recount text are error of omission, error of mis-formation, error of addition and error of mis-ordering. The result of the study indicates that the students made 893 of simple past tense errors which were 0,45% errors of misordering, 3,58% errors of addition, 30,12% errors of omission, and 65,85% errors of mis-formation. The dominant type of errors made by the student is errors of mis-formation. The students’ errors were caused by 36,17% intralingual interference, 58,23% interlingual interference, and 5,6% communication strategies.